2019
DOI: 10.1016/j.carbpol.2018.09.066
|View full text |Cite
|
Sign up to set email alerts
|

Ulvan as novel reducing and stabilizing agent from renewable algal biomass: Application to green synthesis of silver nanoparticles

Abstract: Silver nanoparticles (AgNPs) have been intensively investigated in virtue of their optical and antimicrobial properties, although their applications have been limited due to inherent toxicity and to the need of employing harsh chemical reagents for the synthesis. In this work, ulvan, a sulfated polysaccharide extracted from green algae belonging to Ulva armoricana sp., was for the first time investigated and identified as reducing and stabilizing agent for AgNPs synthesis by using milder conditions than those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(43 citation statements)
references
References 47 publications
3
37
0
1
Order By: Relevance
“…1,2 Silver nanoparticles (AgNPs) have unique physicochemical and biological characteristics with the high surface area due to the variable size ranges from 1 to 100 nm. 3 These unique characteristics of AgNPs have attracted globally and are considered a potent antimicrobial agent. It has been suggested that silver NPs has a significant antimicrobial activity due to multiple reasons including their high affinity with the surface active groups of microbial strains, released of silver ions can rapture the bacterial cell wall or distortion of bacterial DNA helical structure.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Silver nanoparticles (AgNPs) have unique physicochemical and biological characteristics with the high surface area due to the variable size ranges from 1 to 100 nm. 3 These unique characteristics of AgNPs have attracted globally and are considered a potent antimicrobial agent. It has been suggested that silver NPs has a significant antimicrobial activity due to multiple reasons including their high affinity with the surface active groups of microbial strains, released of silver ions can rapture the bacterial cell wall or distortion of bacterial DNA helical structure.…”
Section: Introductionmentioning
confidence: 99%
“…MA-fabricated AgNPs were having the least polydispersity (PDI) reported at 0.209, which shows that they have narrow or uniform dispersity (monodisperse), while MLL NPs (PDI 0.321) and MLB AgNPs (PDI: 0.426) reported moderate dispersity (moderately polydisperse). Our results are in the favor of following studies that report the synthesis of small size nanoparticles with moderate dispersity by using different plant materials (Ali et al, 2016;Massironi et al, 2019;Omran et al, 2019) 3.6 | Comparative analysis Table 1 represents the size of AgNPs measured by various characterization techniques, phytosynthesized by using different species of Lamiaceae family. SEM images showed that the AgNPs are small, nearly spherical, and have a size ≤100 nm, while the AFM images showed small and medium-size nanoparticles.…”
Section: Hydrodynamic Diameter Measurement Of Agnps (Dls Analysis)mentioning
confidence: 69%
“…Among Chlorophyta, the genus Ulva spp. was reported in most of the studies against S. aureus [ 45 , 50 , 66 , 80 , 125 , 126 , 127 , 128 ]. Some studies compared solvent extraction performance for extraction of bioactive compounds: for C. socialis (MeOH > acetone) [ 118 ], U. flexuosa (ethylacetate > MeOH) and for U. rigida (ethanol > Hex> CHCl 3 ).…”
Section: Antibacterial Potential Of Bioactive Compounds From Macromentioning
confidence: 98%